基于铁谱定量分析的齿轮箱磨损分析 - 何照荣; 孙志伟; 宣征南 (Jixie chuandong)
Quantitative analysis of ferrography can obtain the wear values of the gear box during the operation,and the major indicators are DL（index for large grains） and IS（index of wear severity）,which can be drawn for trend curve.According to the failure rate of the device itself and the characteristics of ferrography data,the ferrography data is sifted by residual analysis.And then,the traditional absolute value formula is improved,the wear thresholds value which can reflect the performance of the gearbox is calculated.In practice,the require for estimating the wear conditions of the gearbox can be reached by the improved formula,and the wear conditions during the gearbox performance can be reflected in time.And a method is provided for equipment failure prevention monitoring.